KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI REALISTIC MATHEMATICS EDUCATION (RME) DAN STEAM UNTUK SISWA SEKOLAH DASAR - Arya Putri, Regita; Ladyawati, Erlin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the importance of problem solving skills possessed by participants in preparing for the 21st era which requires students to have problem solving skills. This is caused by a number of factors, among others, low student interest in mathematics subjects, a learning process that still relies on the teacher as a provider of complete information about the material, learning methods that are still ineffective, and the learning model used is still inappropriate. The difficulty usually felt by teachers is the lack of knowledge in using the internet and developing an interesting learning model. This research uses a qualitative approach to the description method. The collection techniques in this study used tests, interviews, and observations. The analysis technique used in this research is data reduction, presenting data, and drawing conclusions. The results of this study indicate that students who have high mathematical problem solving ability are able to solve the two problems given correctly. Learners with moderate solving ability are able to fulfill several indicators of problem solving, while learners with low problem solving ability can be said to be unable to solve the problems given and do not fulfill several problem solving indicators. Keywords: Problem Solving, Learning Model RME, STEAM